IN VITRO COMPARISON OF INDIRECT BONDING METHODS USING DIFFERENT ISOLATION AND ADHESIVE SYSTEMS WITH EACH OTHER AND WITH THE DIRECT BONDING TECHNIQUE - Banu Kılıç; Ercan Cenk Doruk (Ankara University, 2022)
Aim: To compare the shear bond strength and adhesive remnant index of a new indirect bonding isolation method for different adhesive systems with the direct bonding technique. Methods: 100 premolar and 10 centrally extracted human teeth were bonded with one direct and four indirect bonding methods, and then subjected to 1000 thermal cycles between 5°C and 55°C. ARI was analyzed by the chi-square test. The Shear Bond strength was analyzed by the analysis of variance (ANOVA) and the Tukey multiple comparison (HSD) test. The bracket-enamel interface area of two teeth from each group was examined under SEM. Results: All groups provided clinically acceptable bond strengths. In the traditional isolation + light-cured bonding group with the highest bonding values identified, the scores for all failures were recorded as 3 and this group differs from all other groups in respect of ARI scores (p